The principle of Maalat Af’al and its application in dealing with the issue of women converting without their husbands : a case study in the UK - Muhammad Shahrul Ifwat Ishak,; Nur Syahirah Mohammad Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper aims to apply the principle of maalat af’al (consequences of an action) in analysing the issue of women converting to Islam without their husbands from the perspective of maslahah (public interest). Despite the fact that the majority of classical scholars maintain the view that this marriage must be dissolved, dealing with this case in Muslim minority circumstances needs more consideration, particularly in terms of maslahah (securing benefit and removing harm) and mafsadah (harm). Dissolving this marriage immediately could portray a negative image of Islam as a religion that divides families with psychological and emotional impacts on women and their families. This is a qualitative study that obtained data from interviews with several imams and scholars in the UK. The findings indicate that this is a contemporary ijtihadi issue, with some aspects tolerated. Also, the status of maslahah in this issue is in line with the Shari’ah, particularly in facilitating a new Muslim life. While this study is merely exploratory with a limited number of participants, linking theory and reality makes the discussion on the issue and applying the principle of maalat practical.